Evaluation of Dashboard Interactivity for a Local Foodbank. (September 2016) - Desai, Yogeeta; Jiang, Steven; Davis, Lauren
Food insecurity is a serious problem and non-profit humanitarian relief agencies such as foodbanks play a significant role in fighting hunger. Each foodbank collects a lot of data every day. However, the complexity of the data collected from the relief operations provide a challenge for the foodbank managers to make informed decisions. Working with a local foodbank, we have developed dashboards that provide visualized information and allow users to interact with the tool. The effectiveness of the dashboard interactivity was evaluated in an empirical study. Results revealed that different types of interactivity had an impact on user performance. Findings from this research can help designers improve their dashboard design.